2017
DOI: 10.25073/2588-1159/vnuer.4070
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the academic performance of the students

Abstract: Tóm tắt: Giáo dục đào tạo là nhân tố quyết định để phát huy tiềm năng trí tuệ, năng lực sáng tạo của con người. Ngày nay, hơn bao giờ hết trong lịch sử nhân loại, sự giàu mạnh hoặc đói nghèo của một quốc gia phụ thuộc vào chất lượng của giáo dục đại học, mà chất lượng được phản ánh thông qua kết quả học tập của sinh viên. Nhận thức được các yếu tố có ảnh hưởng đến kết quả học tập có thể giúp các nhà giáo dục phát triển các giải pháp nhằm nâng cao chất lượng giáo dục. Mục tiêu chính của nghiên cứu này là nhằm x… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 1 publication
1
5
0
Order By: Relevance
“…The robust influence of peers in real-life academic settings is well-established. Prior research has indicated that teenagers experience substantial social comparison effects (Jansen et al, 2022), strive for academic recognition among their peers (Viet & Phuong, 2017), and engage in increased activities due to peer encouragement (Rukundo, 2012). This effect is likely to be similar in the social media environment.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The robust influence of peers in real-life academic settings is well-established. Prior research has indicated that teenagers experience substantial social comparison effects (Jansen et al, 2022), strive for academic recognition among their peers (Viet & Phuong, 2017), and engage in increased activities due to peer encouragement (Rukundo, 2012). This effect is likely to be similar in the social media environment.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, positive peer influence is seen to have the opposite effect. Viet and Phuong (2017) suggested that peer influence could improve academic performance as adolescents sought to prove their status. Moldes et al (2019) identified peers' support in learning as a factor contributing to positive academic outcomes.…”
Section: Peer Influence Impactsmentioning
confidence: 99%
See 2 more Smart Citations
“…For this, it is necessary to understand and modify the learning styles of students. It is concluded that collaborative learning based on projects [44]- [47], it allows to have a broader vision with the intervention of all those involved when solving a problem not individually but on the contrary as a group. In addition, the techniques that can be used in class sessions by the teacher help students with their learning styles to learn quickly with the support of technological tools [37]- [39].…”
Section: Q2: How Are Teaching Strategies Related To Learning Styles?mentioning
confidence: 99%